Implicit Messages in Pakistani ESL Course Books: A Corpus-Based Study of Gender Representation - Muhammad Tanveer; Urooj Fatima Alvi (Corporum)
The present research seeks to determine the gender representation in English course books in different textbook boards in Pakistan. The corpus-based quantitative study is conducted on the corpus of seven intermediate-level English books. It aims to investigate gender discrimination through gender representation as the Cambridge Dictionary defines gender discrimination as the act of treating a person, usually a woman, unfairly because of their sex. The study explores five dimensions of gender representation: gendered-marked general nouns, pronouns, professional terms, adjectives, and address titles. The study found that gender discrimination exists in the ESL course books, depicting 50% of male general nouns and only 29% of female general nouns. Additionally, gendered-neutral nouns are in lower percentages than male and female nouns. Male pronouns constitute 83%, a more significant percentage than female pronouns. The textbooks predominantly contain male professional terminologies without any feminine or gender-neutral professional terms. Additionally, adjective-based gender discrimination is also obvious in the fact that adjectives are used more often to describe masculine nouns than feminine nouns, about the number of times each word occurs, and shows females as inferior. In addition, the percentage of male address titles is three times higher than that of female and neutral words, depicting that ESL textbook content writers show a male-dominated society. If students repeat gender disparities in textbooks, they may accept gender stereotypes via socialization (Tabatadze & Gorgadze, 2022). The current research work enables authors, educators, and policymakers to write in generic language, create an inclusive learning environment, and add generic lessons to course books, respectively.